Answer:
![g(x)=\frac{1}{2}(3^{-x})](https://tex.z-dn.net/?f=g%28x%29%3D%5Cfrac%7B1%7D%7B2%7D%283%5E%7B-x%7D%29)
Step-by-step explanation:
Given:
The graph of function
are given.
The equation for
is given as:
![f(x)=3^x](https://tex.z-dn.net/?f=f%28x%29%3D3%5Ex)
Now, the graph of
is a reflection of
.
The graph of
passes through the point (-1, 1.5) [second quadrant] and crosses the y-axis at (0, 0.5).
As evident from the graph, the functions
are reflections about the y-axis.
We know the transformation rule for reflection about the y-axis as:
![f(x)\to f(-x)\\\\\therefore 3^x\to3^{-x}....(\textrm{Reflection about y-axis})](https://tex.z-dn.net/?f=f%28x%29%5Cto%20f%28-x%29%5C%5C%5C%5C%5Ctherefore%203%5Ex%5Cto3%5E%7B-x%7D....%28%5Ctextrm%7BReflection%20about%20y-axis%7D%29)
Now, the y-intercept of the function
is obtained by plugging in
. This gives,
![y=3^0=1](https://tex.z-dn.net/?f=y%3D3%5E0%3D1)
So, the y-intercept is at (0, 1). But the graph of
crosses the y-axis at (0, 0.5). As we observe, the coordinate rule for the transformation can be written as:
(0, 1) → (0, 0.5)
![(x,y)\to (x,\frac{1}{2}y)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Cto%20%28x%2C%5Cfrac%7B1%7D%7B2%7Dy%29)
So, the reflected graph is compressed vertically by a factor of
.
Therefore, the transformation is given as:
![y\to \frac{1}{2}y\\\\\therefore 3^{-x}\to \frac{1}{2}(3^{-x})](https://tex.z-dn.net/?f=y%5Cto%20%5Cfrac%7B1%7D%7B2%7Dy%5C%5C%5C%5C%5Ctherefore%203%5E%7B-x%7D%5Cto%20%5Cfrac%7B1%7D%7B2%7D%283%5E%7B-x%7D%29)
Therefore, the equation for
is:
![g(x)=\frac{1}{2}(3^{-x})](https://tex.z-dn.net/?f=g%28x%29%3D%5Cfrac%7B1%7D%7B2%7D%283%5E%7B-x%7D%29)